Formation of fixed assets commercial organizations operating according to Sharia - Sh. A. Shovkhalov (Путеводитель предпринимателя, 2020)
Increasing religious identity of Russia’s population determines the relevance of research questions related with this circumstance. We investigate the issues of formation of own and leased fixed assets of a commercial organization, functioning on Sharia rules in the territory of the Russian Federation.